MODEL PEMBELAJARAN DIRECT INSTRUCTION TERHADAP HASIL BELAJAR AKUNTANSI - Rijal Lubis, Khairunnisa (FKIP UMN ALWASHLIYAH, 2020)
The learning model refers to the approach that will be used, including the learning objectives, the stages in learning activities, the learning environment, and classroom management. Direct Instruction Learning Model is a direct learning model specifically designed to support student learning processes related to declarative knowledge and well-structured procedural knowledge that can be taught with a pattern of activities that are step by step, step by step. The formulation of the problem in this study is